2017
DOI: 10.1007/s11011-017-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

Zeaxanthin improved diabetes-induced anxiety and depression through inhibiting inflammation in hippocampus

Abstract: It is generally accepted that inflammation plays a key role in anxiety and depression induced by diabetes. However, the underlying mechanism and effective treatment method of these diabetes-associated behavior disorders remain to be determined. In the present study, we attempted to illuminate the implication of zeaxanthin in anxiety, depression and neuroinflammation caused by hyperglycemia, and further elaborate the relevant mechanism under these neuropsychiatric disorders. In the current work, diabetic rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 27 publications
2
20
1
2
Order By: Relevance
“…High serum level of bilirubin has been found to be association with depression. 40) This confirmed that mice in the low concentration group showed depressive behaviors, while mice in the high concentration group showed anxious behaviors and decreased learning and memory ability due to nerve damage. Therefore, we hypothesized that low levels of inflammation would lead to depression in mice, while high levels of inflammation would damage neurons in mice, leading to learning and memory impairment and anxiety-like behaviors.…”
Section: Fig 4 Biliverdin Treatment Impaired Memory Formation In Thsupporting
confidence: 54%
“…High serum level of bilirubin has been found to be association with depression. 40) This confirmed that mice in the low concentration group showed depressive behaviors, while mice in the high concentration group showed anxious behaviors and decreased learning and memory ability due to nerve damage. Therefore, we hypothesized that low levels of inflammation would lead to depression in mice, while high levels of inflammation would damage neurons in mice, leading to learning and memory impairment and anxiety-like behaviors.…”
Section: Fig 4 Biliverdin Treatment Impaired Memory Formation In Thsupporting
confidence: 54%
“…Beta-carotene has been shown to reduce the mRNA levels of IL-6 and TNF-α (34). Zeaxanthin can also reduce the expression of IL-6, interleukin-1β (IL-1β), and TNF-α in the hippocampus (35). Second, the development of depression is related to oxidative and an imbalance between antioxidants and prooxidants (36).…”
Section: Discussionmentioning
confidence: 99%
“…But this effect is region speci c, because differences are only present in the hippocampal CA3 and DG area. Hippocampal neurons are key contributor to anxiety and depression, because either inhibition of hippocampal in ammation (Zhou et al 2018;Zhou et al 2017) as well as stimulation of BDNF expression prevented depression-like behavior (Wang et al 2016). Highlighting the key role of hippocampal functioning and mood.…”
Section: Discussionmentioning
confidence: 99%
“…An additional potential mechanism of action is enhanced hippocampal neurogenesis (Liu et al 2016). Also other manipulations can affect in ammation and induce anxiety and depression-like behavior in rodents, such as sleep deprivation (Wadhwa et al 2018;Yin et al 2017;Zielinski et al 2014), chronic mild stress (Wang et al 2018;You et al 2011) and models for chronic in ammatory disease, like diabetes or metabolic syndrome (de Cossío et al Dinel et al 2011;Zhou et al 2018). All those ndings share, that increased in ammation in the hippocampus induces anxiety and depression-like behavior in rodents, and those behavioral symptoms could be attenuated through anti-in ammatory agents which reduced among other pro-in ammatory cytokines IL-6.…”
Section: Discussionmentioning
confidence: 99%